การถอดรหัสสวัสดิการสังคมของประเทศอิตาลีสู่แนวทางการจัดสวัสดิการสังคมสำหรับผู้สูงอายุในประเทศไทย - มาเมือง, ไพทูรย์ (วารสารศรีล้านช้างปริทรรศน์, 2019)
บทความวิชาการฉบับนี้มีวัตถุประสงค์เพื่อศึกษาสภาพการจัดสวัสดิการสังคมสำหรับผู้สูงอายุในอิตาลี เพื่อเปรียบเทียบความเหมือนและความต่างและถอดรหัสสู่การจัดสวัสดิการสังคมสำหรับผู้สูงอายุในในประเทศไทย โดยมีสาระที่เกี่ยวข้องในบทความนี้ ได้แก่ ความหมาย และแนวคิดเกี่ยวกับสำหรับผู้สูงอายุ ปัญหาของผู้สูงอายุ รวมถึงรูปแบบการจัดสวัสดิการสำหรับผู้สูงอายุในอิตาลี จากการศึกษาพบว่า อิตาลีมีความชัดเจนด้านกฎหมายและสวัสดิการเพื่อรองรับปัญหาผู้สูงอายุอย่างเป็นรูปธรรม ตรงกันข้ามกับประเทศไทยที่แม้ว่าแนวโน้มจำนวนผู้สูงอายุจะเพิ่มขึ้นอย่างต่อเนื่อง อีกทั้งสาเหตุ ผลกระทบและความต้องการความช่วยเหลือก็มีบริบทคล้ายคลึงกับอิตาลี ด้วยเหตุนี้ รัฐบาลจึงควรถอดรหัสการจัดสวัสดิการสังคมของอิตาลีเพื่อการดูแลผู้สูงอายุ โดยประยุกต์แนวทางการจัดสวัสดิการของอิตาลีที่สามารถปฏิบัติได้ตามมาตรการ ดังต่อไปนี้ (1) ส่งเสริมการจ้างงานผู้สูงอายุด้วยการลดหย่อนภาษีให้กับภาคเอกชน (2) ออกมาตรการทางกฎหมาย เกี่ยวกับความรับผิดชอบของผู้เป็นบุตรในครอบครัวผู้สูงอายุ เพื่อให้ระบบกฎหมายของไทยมีส่วนต่อการสนับสนุนครอบครัวผู้สูงอายุ ตลอดจนรณรงค์เพื่อสะท้อนความสำคัญของผู้สูงอายุ Abstract           This research objective is to study the social welfare of the elderly in Thailand and Italy. Concepts and data were based on social welfare for elderly in Italy. This allowed us to compare and understand the occurrences in order to provide better care for our own social welfare program for elderly in Thailand. Ergo, this allows a case study review between the cause and effect of elderly and social welfare for elderly between Italy and Thailand. It is found that in Italy case files, the clarification regarding national law and welfare is objective towards this exact problem. This is contrary to the situation in Thailand. While the tendency of most elderly was greater; the cause and effect requirements are similar; however, there is no specific welfare plan for these particular group of elderly. Therefore, the government of Thailand should apply a social welfare program learned from Italy’s very own elderly solutions with the following: 1. Tax deduction for private sectors to hire elderly. 2. Issue legal measures for compulsory performance of family responsibility to enable the Thai legal system to contribute to the support of elderly families as well as campaigning to reflect the importance of the elderly in Thailand.